Conversas entre arquitetos e engenheiros no ensino de projetos - Marina Ferreira Borges (2019)
Structural education is a key element for stimulating architecture students to think about the relations between form, materiality and tectonics, leading to a point of convergence between the disciplines of architectural design and structural engineering, whose lack of organicity only accentuates the fragmentation between design and construction. The teaching plans of the disciplines of structures emphasize that the aim of these disciplines in the courses of architecture is to promote the dialogue between architects and engineers in the practice of design through a common language between them. But in teaching practice, is this desirable dialogue between architectural design disciplines and structural education effectively taking place? Can the existing models to teach structures absorb the changes and possibilities opened by new technologies and their impact on architectural design practice? Would changing teaching methods be enough to correct harmful traits of the field's production and reproduction mechanisms? To develop a new educational model that integrates architectural, structural and digital issues, we proposed the realization of hybrid disciplines, experimented between the years 2016 and 2018, in the architecture courses of UFMG and PUC Minas. The model developed among these disciplines allowed an effective dialogic practice of design, enabling architecture students to elaborate new project systems that encourage the construction of a collective practice of knowledge through cooperative processes between architects and engineers, interacting with computational tools of simulation of structural behavior as a way to assist in making decisions in complex design situations.